A Successful Collaborative Approach to the Perioperative Management After Hip Arthroscopy of a Patient with Heterozygous Prothrombin G20210A Mutation: A Case Report. Issue 2 (April 2019) - Parsa, Ali; Nazal, Mark R.; Stelzer, John W.; Sieff, Colin A.; Martin, Scott D.
Abstract : Case: We report on a patient with heterozygous prothrombin G20210A mutation (PTM) and a history of venous thromboembolism (VTE) after knee arthroscopy, who was undergoing hip arthroscopy. This common mutation has an overall prevalence of 2.0% and results in a 280% to 420% likelihood of thrombosis compared to patients without the mutation. Conclusions: Hip arthroscopy is associated with a low risk of VTE with currently no guidelines for thromboprophylaxis. Patients should be managed in relation to their risk factors utilizing a collaborative, individualized approach. Treatment with short-term low-molecular-weight heparin resulted in no thromboembolism at 18-month follow-up for this patient with PTM.